1997
DOI: 10.1002/(sici)1097-0355(199723)18:3<282::aid-imhj5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Marital adaptation, divorce, and parent–infant development: A prospective study

Abstract: In this prospective study of divorce in the first 4 years of life we have shown that previous marital patterns anticipate the occurrence of divorce and influence the response to that event. Most of the divorces occurred in marriages that were consistently low in satisfaction or decreased in satisfaction from birth on. The family response to the event differed. The continuing effort at conflict resolution and the fact that differing levels of adjustment are reached at different time points are suggested by thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
1
5
0
3
Order By: Relevance
“…This result relates to the findings of other family researchers indicating that for some couples, the risks associated with ongoing marital conflict may supersede the risks of divorce (Heinicke, Guthrie, & Ruth, 1997). However, it is premature to suggest---on the basis of our results-that young mothers with hostile-antisocial partners are likely to function better as parents if they are not cohabiting.…”
Section: Paternal Risk and Maternal Functioningsupporting
confidence: 72%
“…This result relates to the findings of other family researchers indicating that for some couples, the risks associated with ongoing marital conflict may supersede the risks of divorce (Heinicke, Guthrie, & Ruth, 1997). However, it is premature to suggest---on the basis of our results-that young mothers with hostile-antisocial partners are likely to function better as parents if they are not cohabiting.…”
Section: Paternal Risk and Maternal Functioningsupporting
confidence: 72%
“…Infants and toddlers are especially vulnerable to parental divorce and family disruption [133,134]. In the general population, studies show that parental divorce is the source of vulnerability for some children and resilience for others [133][134][135][136][137][138][139]. In cases when intimate partner violence is present within the dyadic relationship, divorce has the potential to protect the young child from witnessing violence and further trauma.…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…Predivorce marital functioning also may affect children's adjustment to divorce. A longitudinal study of 92 families (Heinicke, Guthrie, & Ruth, 1997) found that children whose parents had low‐quality marriages and divorced demonstrated fewer behavior problems and more prosocial behavior than did children whose parents had low‐quality marriages and stayed together. This study had several strengths, such as the longitudinal design and the use of multiple methods, including observations of couple and parent‐child relationships.…”
Section: Parental Divorce and Developmental Outcomes In Early Childhoodmentioning
confidence: 99%
“…Specifically, the dimensions of parenting quality that are important for children's adjustment to divorce may differ by children's developmental stage. Studies of older children have assessed parental monitoring of children's activities and parental involvement (e.g., Capaldi & Patterson, 1991; Kurtz, 1994; Martinez & Forgatch, 2002; Simons, Lin, Gordon, Conger, & Lorenz, 1999), whereas studies of younger children typically have focused more on parental warmth and responsiveness (Heinicke et al, 1997; Hodges et al, 1983; Pett et al, 1999; Whiteside & Becker, 2000) or cognitive stimulation (Clarke‐Stewart et al, 2000; Poehlmann & Fiese, 1994). It is likely that parental warmth and responsiveness are important protective factors throughout childhood and adolescence, but parental monitoring and involvement becomes more important in middle childhood and adolescence as children spend more time involved in activities outside the home and with peers.…”
Section: Multiple Influences On Adjustmentmentioning
confidence: 99%